2016
DOI: 10.1152/ajprenal.00502.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 and diabetic nephropathy

Abstract: Transforming growth factor-β1 (TGF-β1) is established to be involved in the pathogenesis of diabetic nephropathy. The diabetic milieu enhances oxidative stress and induces the expression of TGF-β1. TGF-β1 promotes cell hypertrophy and extracellular matrix accumulation in the mesangium, which decreases glomerular filtration rate and leads to chronic renal failure. Recently, TGF-β1 has been demonstrated to regulate urinary albumin excretion by both increasing glomerular permeability and decreasing reabsorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 121 publications
5
127
1
Order By: Relevance
“…26 Among such cytokines, the transforming growth factor-β1 (TGF-β1) is believed to have a central role as a mediator in the fibrogenic process of diabetic nephropathy. 27 In the current study, TGF-β1 was not detected in the renal cortex of control group I. On the other hand, diabetic rats in group III showed a positive TGF-β1immune-reaction in affected renal corpuscles and tubules.…”
Section: Discussioncontrasting
confidence: 53%
“…26 Among such cytokines, the transforming growth factor-β1 (TGF-β1) is believed to have a central role as a mediator in the fibrogenic process of diabetic nephropathy. 27 In the current study, TGF-β1 was not detected in the renal cortex of control group I. On the other hand, diabetic rats in group III showed a positive TGF-β1immune-reaction in affected renal corpuscles and tubules.…”
Section: Discussioncontrasting
confidence: 53%
“…It is considered to be the strongest cytokine involved in glomerulosclerosis in diabetic nephropathy [19]. We found that the TGF-β1 level in diabetic rats was significantly higher than in the controls.…”
Section: Changes In Icam-1 Mcp-1 Tgf-β1 In Rat Renal Tissuementioning
confidence: 60%
“…4 F‐H ). We found that TGF‐β, a key mediator of extracellular matrix overproduction and glomerulosclerosis (25), was dramatically increased in diabetic mice but was significantly lower in Nlrc5 ‐/‐ ‐STZ compared with WT‐STZ mice (Fig. 4 I, J ).…”
Section: Resultsmentioning
confidence: 95%